2006
DOI: 10.1111/j.1524-4725.2005.31156
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Predictors of Basal Cell Carcinoma Diagnosis

Abstract: This is the first study to determine a relevant PPV for the clinical diagnosis of BCC because the PPV was based on clinical confidence level. These results highlight the role of diagnostic biopsies, could improve patient referral, and may help increase the PPV in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Physical examination for NMSC can be performed by an expert, by a general practitioner or by the patient. Results from the selected studies 2,6–14 are presented in Table 1. The false‐negative diagnostic rates as well as the false‐positive rates cannot be ignored as it was demonstrated in a study where 3% of lesions assessed as benign proved malignant and 40% of suspected malignancies were benign 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Physical examination for NMSC can be performed by an expert, by a general practitioner or by the patient. Results from the selected studies 2,6–14 are presented in Table 1. The false‐negative diagnostic rates as well as the false‐positive rates cannot be ignored as it was demonstrated in a study where 3% of lesions assessed as benign proved malignant and 40% of suspected malignancies were benign 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the naked-eye clinical diagnosis of BCC is essential in daily clinical practice, there is little published data regarding its accuracy. Schwartzberg et al investigated the confidence of dermatologists at the University of Miami in the clinical diagnosis of BCC using a retrospective questionnaire which resulted in a PPV of 80% based on clear-cut clinical BCC features (29). Other studies evaluating clinical examinations revealed a sensitivity ranging between 63.9% and 91.1% and PPV ranging between 72.8% and 73.9% (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several studies have demonstrated that the clinical diagnosis of BCC is accurate in 70-89%. [18][19][20][21] However, a correct clinical BCC diagnosis does not imply a correct clinical diagnosis of histological subtype. It would be interesting to know whether the clinical BCC subtype is as reliable as or even more reliable than the histological BCC subtype determined on a punch biopsy.…”
Section: Discussionmentioning
confidence: 99%